Sliding mode control of multi-agent system with application to UAV air combat. (December 2021) - Liu, Chang; Sun, Shaoshan; Tao, Chenggang; Shou, Yingxin; Xu, Bin
Abstract: This paper investigates the air combat mission between the multiple Unmanned Aerial Vehicle (UAV) and hostile multi-UAV. The multi-UAV air combat threat assessment model is firstly established to evaluate the situation of each drone in the combat scenario and then, the target allocation problem is formulated based on matrix game theory. To solve the target allocation problem, the modified Estimate of Distribution Algorithm (EDA) is proposed to search the best strategy. After the target allocation, the social behavioral based sliding mode control is finally constructed to realize the UAV swarm motion. The simulation experiment of multi-UAV air combat proves the validity of the algorithm.